Analisis kemampuan pemecahan masalah siswa dalam menyelesaikan masalah non-rutin statistika - Esterlina Esterlina; Jarnawi Afgani Dahlan; Bambang Avip Priatna Martadiputra (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study observes students' problem-solving abilities in solving non-routine statistic problems. In this paper used descriptive qualitative by considering the population in one of the VIII I grade junior high schools in Bandung, namely SMP 12 Bandung by categorizing the results of problem-solving abilities into two categories, namely high and low. The sampling technique used purposive sampling involving 29 students. This research used problem-solving tests and interview guides to collect data. Test question was describing mathematical problem solving, consisting of one question on the Polya stages, which is used as a tool. This paper presents that students with high problem-solving skills in this study indicate that students with junior high problem-solving skills fall into the "good" category. At the same time, students with not good problem-solving problems, we can call it as "not good" category. The caused was the inability of students in the initial stage of problem-solving indicators, namely the process of understanding problems, usually students have difficulties in understanding and identifying problems, and difficulties in converting abstract tasks into mathematical form.